THE EFFECT OF DIFFERENT FEED ON BROOD STOCK TO OVULATION, INCUBATION AND LARVAL SURVIVAL RATE OF INGIR-INGIR FISH (Mystus nigriceps) - Nurlisa Harahap; Nuraini '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research of effect of different feed on brood stock to ovulation, incubation and larval survival rate of Ingir-ingir fish (Mystus nigriceps) has been implemented in Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Sciences University of Riau, Pekanbaru from January until March 2016. This study used a complete randomized design with four treatments consisting of feeding the form earthworms (Lumbricus rubbelus), feeding the form Hairy Cockle (Anadara antiquata), and feeding the form million fish (Poecilia reticulata). Each treatment was repeated three times. The results showed that difeerent feed brood stock Ingir-ingir fish (Mystus nigriceps) produces the best on feeding the form million fish (Poecilia reticulata) which produce latency time 6, 47 (hours, minutes), the number of eggs striping result average of 1061 eggs/g broodstock, fertilization rate average of 19,38%, hatching rate average of 53,96% and larval survival rate average of 66,85%.Keywords: Mystus nigriceps, feed, ovulation, incubation, survival rate